The Risks that Should be Taken into Account and Conditions that Needs to be Met before the Government Launches a Programme to Attack Corruption in the Civil Service: Array - Mcbell Ninepence, Albert (Acta Universitatis Danubius. Administratio, 2021)
Transparency International (2008) defines corruption as “the misuse of entrusted power for private gain”. The menace of corruption is central on the agenda of policymakers and scholars. In view of this, the recent anti-corruption summit in London in May 2016 underscored the need to mitigate corruption as an essential tool for sustaining economic stability and growth. The causes of corruption has been imputed to low salaries, greed, and senior public officials’ immunity from prosecution among others. Governments around the world have set up anti-corruption agencies and policies however, corruption continues to be rampant in many countries. While scholars like Vogl et al (2000) argue the difficulty of setting up anti-corruption agencies and countries that have it in place have failed to mitigate corruption, (Svensson, 2005) contends that the level of corruption in a country is determined not only by GDP per capita and human capital but by political competitions and markets in a country. Moreover, a number of studies have elucidated the effectiveness of various anti-corruption strategies in countries with low levels of corruption (Franken, 2009, Herzfeld and Weiss 2003, Van Rijckeghem and Weder, 2001). This paper therefore seeks to independently address the risks that should be incorporated and the conditions that needs to be met by government in an attempt to launch a programme to combat corruption in the civil service.